Timidez na educação infantil: contribuição e intervenção por meio lúdico - Barbosa, Ana Carolina Vieira [UNESP]; Wiezzel, Andréia Cristiane Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Shyness, in general, it is not observed in the classroom, for the timid child does not cause problems, does not call the attention. However, care must be taken that excessive shyness not harm in the future as it involves low self-esteem, difficulties to relate, fear, deprivation, limiting emotional development, and hence relationships at school. The research presented is a case study based on Winnicott's psychoanalysis and the proposal has to demonstrate how, through play, we can help in interpersonal relationships of shy children, enabling, through play, express their feelings and win security. As data collection instruments interviews were conducted with the parent and the teacher and recreational activities with the selected child in school playroom. The data were categorized and analyzed based on Winnicott's theory. At the end of the study, the teacher mentioned that the child attended was quite spontaneous and communicative, very different from what it stood at the beginning of the school year.

A timidez, em geral, não é observada em sala de aula, pois, a criança tímida não causa problemas, não chama à atenção. Todavia, cuidados devem ser tomados para que a timidez excessiva não a prejudique no futuro, pois envolve baixa-estima, dificuldades de se relacionar, medo, privações, o que limita o desenvolvimento emocional e, consequentemente, os relacionamentos na escola. A pesquisa apresentada é um estudo de caso baseado na psicanálise de Winnicott e tem a proposta de demonstrar como, através do lúdico, podemos auxiliar nas relações interpessoais de crianças tímidas, possibilitando, por meio do brincar, expressarem seus sentimentos e conquistarem segurança. Como instrumentos de coleta de dados foram realizadas entrevistas com o pai e a professora e atividades lúdicas com a criança selecionada na brinquedoteca escolar. Os dados foram categorizados e analisados com base na teoria winnicottiana. Ao final da pesquisa, a professora mencionou que a criança atendida estava bastante espontânea e comunicativa, muito diferente do que se apresentava no início do ano letivo.
Shyness in children's education: contribution and intervention through playful
Keywords: Shyness; Early childhood education; Recreational activities; Timidez; Educação infantil; Atividades lúdicas